A Qualitative Study of Hospice Perceptions and Image of the Elderly in Health Care College Students (Medico Legal Update, 2019)
The problems in an aging society are regarded as social issues to be tackled according to the obligations andrights in the balance between the nation’s publicity nature and individuals’ dignity and social responsibility.This is descriptive research aimed at investigating the image of the elderly in healthcare majors aged ?25years by their general characteristics and at determining the associations among the sub-areas of the image.They scored an average of 4.11 ± .29 for the general image of the elderly. For the sub-areas, they scoredhighest for generosity (4.19 ± .71), followed by vitality (3.70 ± .60) and flexibility (3.07 ± .92). For the items,they scored highest for cold-warm (4.95 ± 1.38), followed by estranged-intimate (4.67 ± 1.49), wise-foolish(4.64 ± 1.27), and gentle-strict (4.37 ± 1.52). They scored lowest for slow-quick (2.80 ± 1.22), unoccupiedbusy(2.83 ± 1.49), conservative-progressive (2.88 ± 1.48), and stubborn-obedient (2.96 ± 1.36). The scoredan average of 3.16 ± .29 for the hospice perception. There were statistically significant differences in gender(t = -2.24, p = .02) and growing urban size (t = 2.44, p = .02). There was no statistically significant differencein hospice perception according to general characteristics. The correlation between the image of the elderlyand the hospice perception was not statistically significant. Based on the results of this study, it is suggestedto develop a customized education program reflecting the image of the elderly and Hospice perception.Future research will develop a curriculum that integrates the awareness of the elderly and social perceptionof hospice. We suggest the need to gain insight into these curriculums during the age of super aging.